Peran Work–Life Balance terhadap Kepuasan Kerja Perawat - Aulia Rizky Kurnia Jati; Arlina Dhian Sulistyowati; Suyami; Cahyo Pramono (Universitas Muhammadiyah Klaten, 2026)
High work demands among healthcare professionals, particularly nurses, may affect Work-life balance and Job satisfaction. Nurses are required to provide optimal care while facing long working hours, shift systems, and high emotional demands. An imbalance in Work-life balance can reduce Job satisfaction, increase work-related stress, and negatively impact the quality of healthcare services. This study aimed to examine the relationship between Work-life balance and Job satisfaction among female nurses at PKU Muhammadiyah Prambanan Hospital, Klaten. This study employed an analytical correlational design with a cross-sectional approach. The study population consisted of all female nurses, with a total sample of 35 respondents selected using total sampling. The research instruments were Work-life balance and Job satisfaction questionnaires that had been tested for validity and reliability. Bivariate data analysis was conducted using the Spearman Rank test. The results showed that the mean age of respondents was 25.63 ± 3.719 years. Most respondents were unmarried (65.7%), had no children (85.7%), held a Diploma in Nursing (74.3%), had a length of employment of 0–1 year (54.3%), and worked in inpatient units (48.6%). The majority of respondents had good Work-life balance (80%) and high Job satisfaction (88.6%). The Spearman Rank test indicated a positive and significant relationship between Work-life balance and Job satisfaction (p = 0.011), meaning that better Work-life balance was associated with higher Job satisfaction among nurses. In conclusion, there is a significant relationship between Work-life balance and Job satisfaction among nurses. Therefore, healthcare institutions should implement work policies that support Work-life balance to enhance nurses’ Job satisfaction.